1998
DOI: 10.1071/pp97167
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water deficits on 13C discrimination and transpiration efficiency of Eucalyptus globulus clones

Abstract: Potted cuttings of three Eucalyptus globulus Labill. clones (AR3, CN44, MP11) were grown over 6 months in a greenhouse under three watering regimes: well watered (HW), moderate soil water deficit (MS) and severe soil water deficit (SS). Transpiration efficiency (W = total dry matter/water transpired) and leaf intrinsic gas exchange efficiency (A/gs = carbon assimilation rate/stomatal conductance) increased under water stress and were positively correlated with the stable carbon isotope composition of leaf tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 0 publications
6
38
1
2
Order By: Relevance
“…It is related to the ratio of intercellular and atmospheric CO 2 concentrations (C i /C a ) and is therefore dependent on both A and g s (Farquhar et al 1982). It is well documented that water stress changes water use efficiency and carbon isotope composition in different species (Farquhar and Richards 1984;Osório et al 1998). In grapevines, Gibberd et al (2001) observed a negative linear relationship between transpiration efficiency and 13 C discrimination.…”
Section: Discussionmentioning
confidence: 93%
“…It is related to the ratio of intercellular and atmospheric CO 2 concentrations (C i /C a ) and is therefore dependent on both A and g s (Farquhar et al 1982). It is well documented that water stress changes water use efficiency and carbon isotope composition in different species (Farquhar and Richards 1984;Osório et al 1998). In grapevines, Gibberd et al (2001) observed a negative linear relationship between transpiration efficiency and 13 C discrimination.…”
Section: Discussionmentioning
confidence: 93%
“…Hubick et al 1986, Körner et al 1988, 1991, Hultine and Marshall 2000, it has been the most common measure to describe differences in water use strategies (Marshall and Zhang 1994, Sun et al 1996, Osorio et al 1998, Li et al 2000, Li and Wang 2003. Consistent with this, many previous studies reported that δ 13 C increases with altitude, and is often correlated with leaf morphological and physiological properties that vary with altitude (Vitousek et al 1990, Meinzer et al 1992, Sparks and Ehleringer 1997, Cordell et al 1998, Li et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Plant tissue δ 13 C provides an integrated measurement of internal plant physiological and external environmental properties influencing photosynthetic gas exchange over the time when the carbon was fixed (Anderson et al 1996, Brodribb andHill 1998). Considerable effort has gone into the description of sources of variation in δ 13 C, which varies among co-occurring species (Stewart et al 199, Schulze et al 1998, Li et al 2004, and genotypes within species (Zhang et al 1993, Osorio et al 1998, Li et al 2000 along environmental gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the isotopic composition reflects the effect of the plant water status on photosynthesis throughout the growing season (Farquhar and Richards, 1984). In the present study it was used to evaluate the intrinsic plant water use efficiency as it was for many plant species in response to different environmental conditions (Zhang et al, 1994;Le Roux et al, 1996;Osório et al, 1998;Martin et al, 1999;Robinson et al, 2000;Araus et al, 2003), including grapevines (Gaudillère et al, 2002).…”
Section: Introductionmentioning
confidence: 99%